STATE-OF-THE-ART REVIEW OF GRADUATE TEACHER EDUCATION RESEARCHES: RELEVANCE TO THE NATIONAL RESEARCH PRIORITIES OF NATIONAL HIGHER EDUCATION RESEARCH AGENDA-II - VANNESSA D. UMALI (Jurnal Studi Pemerintahan, 2020)
The state-of-the-art review assesses the graduate research outputs in education produced by graduate teacher education students in selected public and private schools in the National Capital Region during the School Year 2007-2016 based on national research priorities of National Higher Education Research Agenda-II. To provide a means of evaluating existing programs and to validate the result of the state of the art review of graduate education outputs- – an expert validation was made among the Research and Development Directors from three (3) institutions involved in the review. Methods are identifying, classifying, and examining the content of data and how it responds according to research priorities set by National Higher Education Research Agenda-II. The rising importance of research innovation in the country has underpinned HEIs in restructuring and prioritization. There is a need for closer monitoring the graduate teacher education researches to areas relevance for the improvement.